PENGARUH NILAI RELIGIUSITAS PADA BRAND SWITCHING KONSUMEN MUSLIM ACEH PASCA FATWA MUI NO. 83 TAHUN 2023 - Ritonga, Nursakinah; Cut Andyna (FISIP Universitas Malikussaleh, 2025)
The international BDS (Boycott, Divestment, Sanctions) movement is an effort of resistance that does not use violence but by boycotting products affiliated with Israel. In line with the BDS movement, the Fatwa commission of the Indonesian Ulema Council (MUI) on November 8, 2023 issued the latest fatwa number 83 of 2023 regarding the Law of Support for the Palestinian Struggle which emphasizes that supporting Israeli aggression against Palestine is haram, including purchasing food and beverage products affiliated with Israel. Aceh Province is an autonomous region based on the principles of Islamic law in Indonesia. This study aims to explain and analyze the effect of Religiousness Value on consumer behavior in doing Brand Switching of food and beverage products.Brand Switching food and beverage products. The population in this study were Acehnese Muslims who made brand switches in purchasing transactions for food and beverage products, where the population size was not known with certainty. The number of research samples was 100 respondents using the Lemeshow formula. Data collection methods using online and ofline questionnaires. The data analysis method used in this study consists of an instrument test in the form of a validity test and reliability test, normality test, then hypothesis testing. The results showed that Brand Switching of food and beverage products was strongly influenced by the religiosity value of Acehnese Muslim consumers after the issuance of MUI Fatwa No.83 of 2023.